Respostas
respondido por:
0
5x + 2y = 3
10x + 6y = 14
pelo método da adição, multiplica a primeira equação por - 3
- 15x - 6y = - 9
10x + 6y = 14
soma as duas
- 5x = 5 (-1)
5x = - 5
x = - 5 / 5
x = - 1
agora achamos y
5.(-1) + 2y = 3
- 5 + 2y = 3
2y = 3 + 5
y = 8 / 2
y = 4
S = {- 1, 4}
10x + 6y = 14
pelo método da adição, multiplica a primeira equação por - 3
- 15x - 6y = - 9
10x + 6y = 14
soma as duas
- 5x = 5 (-1)
5x = - 5
x = - 5 / 5
x = - 1
agora achamos y
5.(-1) + 2y = 3
- 5 + 2y = 3
2y = 3 + 5
y = 8 / 2
y = 4
S = {- 1, 4}
CLAWDYNEYA:
OBRIGADO
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás